Analisis Strategi Eksternal dan Internal untuk Pengembangan Berkelanjutan pada UMKM Sabana Fried Chicken Panyileukan - Nurshanti, Devia Izmi; Agustin, Imel Aura; Elsa, Nadia; Aisy, Risnawati; Sampurna, Yoga; Mardiana, Siti (Teewan Journal Solutions, 2025)
This study aims to analyze external and internal strategies in UMKM Sabana Fried Chicken Panyileukan in order to formulate a sustainable development strategy. The approach used is descriptive qualitative with interview methods, direct observation, and literature studies. The analytical tools used include PESTLE, Porter's Five Forces, Competitor Mapping, Industry Matrix, VRIO, Value Chain, Business Model Canvas (BMC), and IFAS and EFAS Tables formulated into SWOT and TOWS Matrices. The results of the analysis show that Sabana has advantages in strategic location, customer loyalty, and efficient operational systems. However, there are significant weaknesses in terms of promotion, digitalization, and dependence on the owner. From the external side, Sabana is considered quite responsive to opportunities such as fast food trends and stable raw material prices, even though it is faced with threats of competition and environmental issues such as flooding. Based on the IE Matrix, the business position is in Quadrant V (Hold and Maintain), which recommends a survival strategy through optimizing strengths and gradually improving weaknesses. The recommended strategies include strengthening digital promotion, HR training, and implementing a digital operational system. This research is expected to be a strategic reference for MSMEs in designing adaptive and sustainable business decisions.